Pengaruh Metode Sosiodrama Terhadap Kreativitas Belajar Siswa Kelas VIII SMP Negeri 3 Paranginan Kabupaten Humbang Hasundutan T.P 2024/2025 - Melpa Sintauli Hasibuan; Rida Gultom; Damayanti Nababan; Tiurma Barasa; Lasmaria Lumbantobing (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study was to determine the significant positive influence between the Sociodrama Method on the Creativity of Class VIII students of SMP Negeri 3 Paranginan, Humbang Hasundutan Regency, Academic Year 2024/2025. The method used in this study is a quantitative research method and the type of research is a pre-experimental design with the form of